School Principal's Strategy Shapes TAS Performance in Carrying Out Dual Tasks (School Operators) - Azizah, Putri Nur; Sultoni, Sultoni; Triwiyanto, Teguh (Universitas Negeri Malang, 2024)
The Principal has a role in shaping the performance of School Administration Personnel, especially in carrying out dual duties as school operators, the dual tasks received by TAS often add to the workload and responsibilities quite large, so it requires an effective managerial strategy from the principal including improving competence through training, clear division of tasks, and the implementation of a periodic supervision and evaluation system. This study uses a descriptive qualitative method to analyze the principal's efforts in shaping TAS performance, by using literature studies to understand what is known about the topic, as well as identify gaps in knowledge, and help researchers formulate questions or hypotheses more sharply. The purpose of this study is to find out the strategies and efforts of school principals in dealing with the determination of dual tasks given to TAS, which will later find several strategies and steps for school principals in supporting TAS performance. The results of this study will show the strategy of school principals in shaping TAS performance in carrying out dual tasks such as, improving TAS performance through the leadership role of the principal, time management and division of labor priorities, improving performance through training and development, and creating a supportive work environment.